Iceland : Technical Assistance Report on a New Organic Budget Law. (IMF Staff Country Reports; Country Report ;, 2012)
This technical assistance report on Iceland focuses on a new organic budget law (OBL). In designing a new OBL, it is important to preserve good features of Iceland's current legal framework for budgeting. At the same time, any new OBL should address the key weaknesses in the Financial Reporting Act 1997 that prevent it from providing a credible, integrated framework for budgeting. The institutional coverage of the OBL should be expanded to encompass the whole public sector and incorporate an integrated timetable for the entire budget process.